Design and analysis of high output piezoelectric energy harvester using non uniform beam. Issue 3 (3rd February 2020) - Raju, S. Srinivasulu; Umapathy, M.; Uma, G.
ABSTRACT: Among the energy harvesting techniques, design of piezoelectric energy harvesters using cantilever beam is popular. In this paper two different structurally tailored cantilever based piezoelectric energy harvesters are proposed to improve the harvested power. In the first design, the harvester consists of rectangular section from the root followed by a tapered section (RTCB) and in the second type tapered section followed by rectangular section (TRCB). These harvesters are associated with a piezoelectric patch to achieve higher power by means of connecting the uniform width of rectangular section to the width tapered beam having tapering ratio β towards its free end. It is also proposed to introduce a rectangular cavity in the above energy harvesters to further maximize the harvester voltage. The mode shapes and fundamental natural frequency of proposed energy harvesters are obtained analytically by using Euler-Bernoulli beam theory and its free vibration solution is analyzed by using Bessel functions. The performance of the proposed energy harvesters is demonstrated through both analytical and experimental implementation. Harvester TRCB increases the harvester voltage by 91.3% and 76.9% respectively as compared to the energy harvester considered with uniform cantilever beam. Among all the energy harvesters projected during this paper, the maximum voltage is produced from the TRCB harvester with rectangular cavity.